Application of Kumpai (Hymenachne sp.) Grass Liquid Organic Fertilizer on Swamp Water as Culture Medium of Pangasius Catfish (Pangasius sp.) With an Aquaponic System - Jubaedah, Dade; Yulisman; Amin, Mohamad; Marsi; Shadila, Tika Aprilia (International Journal of Aquatic Research and Environmental Studies, 2026)
Nutritional needs in an aquaponic system can be fulfilled through the application of liquid organic fertilizer. This study aimed to determine the best dose of kumpai grass liquid organic fertilizer on the culture of pangasius catfish and lettuce plants using a floating raft aquaponic system. This study used a Completely Randomized Design with four treatments and three replications. The treatments consist of liquid organic fertilizer (P0), kumpai grass liquid organic fertilizer 3 μL L-1 per day (P1), 5 μL L-1 per day (P2), and 7 μL L-1 per day (P3). Pangasius catfish with an initial length 5±0.5 cm and stocking density of 100 fish per m3 was cultured for 42 days. The results showed that application of kumpai grass liquid organic fertilizer (LOF) 5 μL L-1 per day (P2) was the best treatment with water quality at day 42 culture. Kumpai grass Liquid organic fertilizer provides essential nutrients, especially for cultivation media using swamp water. Besides maintaining water quality, it also supports the growth and sustainability of catfish and the harvest of lettuce plants.
Keywords: aquaponic, kumpai grass, liquid organic fertilizer